Buyang Huanwu Tang inhibits cellular epithelial-to-mesenchymal transition by inhibiting TGF-β1 activation of PI3K/Akt signaling pathway in pulmonary fibrosis model in vitro - Yin, Zi-fei (BMC Complement Med Ther, 2020)
BACKGROUND: Pulmonary fibrosis (PF) is a chronic and progressive interstitial lung disease. Buyang Huanwu Tang (BYHWT), a classical traditional Chinese medicine formula, has been widely utilized for the treatment of PF in China. This present study aimed to explore the mechanism of BYHWT in the treatment of PF in vitro. METHODS: TGF-β1 stimulated human alveolar epithelial A549 cells were used as in vitro model for PF. Post the treatment of BYHWT, cell viability was measured by MTT assay, and cell morphology was observed under microscope. The epithelial-to-mesenchymal transition (EMT) markers (E-cadherin, Vimentin) and collagen I (Col I) were detected by western blot, immunofluorescence staining and real-time quantitative polymerase chain reaction. With the co-administration of activators (IGF-1, SC79) and inhibitors (LY294002, MK2206), the effect of BYHWT on PI3K/Akt pathway was analyzed by western blot. RESULTS: BYHWT inhibited cell growth, and prevented cell morphology changed from epithelial to fibroblasts in TGF-β1 induced A549 cells. BYHWT decreased Vimentin and Col I, while increased E-cadherin at both protein and mRNA levels. Moreover, phosphorylation of PI3K (p-PI3K) and phosphorylation of Akt (p-Akt) were significantly down-regulated by BYHWT in TGF-β1 stimulated A549 cells. CONCLUSION: These results indicate that BYHWT suppressed TGF-β1-induced collagen accumulation and EMT of A549 cells by inhibiting the PI3K/Akt signaling pathway. These findings suggest that BYHWT may have potential for the treatment of PF.